Burst or High‐Frequency (10 kHz) Spinal Cord Stimulation in Failed Back Surgery Syndrome Patients With Predominant Back Pain: One Year Comparative Data. Issue 7 (24th May 2017) - Muhammad, Sajjad; Roeske, Sandra; Chaudhry, Shafqat Rasul; Kinfe, Thomas Mehari
Abstract : Objectives: Burst and 10 kHz spinal cord stimulation (SCS) demonstrated improvement for failed back surgery syndrome (FBSS) with predominant, refractory back pain. Here, we report the long‐term follow‐up of a previously published study comparing the safety and efficacy of burst vs. 10 kHz SCS for predominant back pain (70% of global pain) of FBSS patients. Methods: This comparative, observational study extended the follow‐up period up to 20 months evaluating both SCS modalities. Pain intensity (visual analog scale [VASB, VASL ]), functional capacity (Pittsburgh Sleep Quality Index [PSQI]; depression (Beck Depression Inventory [BDI]), stimulation parameters and hardware and/or stimulation associated adverse events were recorded and analyzed over time. Results: Overall VASB ( t 1, 12  = 66.76, p  < 0.001) and VASL ( t 1, 12  = 4.763, p  < 0.049; p  < 0.001) declined over time. Burst significantly decreased VASB by 87.5% (±17.7) (mean 8 ± 0.76 to 1 ± 1.41; t 1 =12.3, p  < 0.001), and 10 kHz significant decreased VASB by 54.9% (±44) (mean 8 ± 0.63 to 3.5 ± 3.27; t 1 =3.09, p  = 0.027). No significant differences for between SCS types were revealed ( t 1 =1.75, p  = 0.13). VASL was significantly suppressed for burst (burst: 3.6 ± 1.59 to 1.5 ± 1.06; t 1  = 3.32, p  = 0.013). A significant effect of time was found for functional outcome with no significant differences between SCS types (PSQI: t 1, 12  = 8.8, p  = 0.012; and BDI: t 1  = 53.3, p  < 0.001). No stimulation/hardware‐related complications occurred. Discussion: Long‐term data of this comparative study suggests that burst responsiveness was superior to 10 kHz in our small‐scale cohort, thus a larger, randomized‐controlled comparative study design is highly recommended.